The Trade Impact of China on EMU : Is It Even Across Members? - Perez Ruiz, Esther (IMF Working Papers; Working Paper ;, 2012)
This paper investigates the asymmetries in trade spillovers from sector-specific technology shocks in China to selected euro area countries. We use a Ricardian-gravity trade model to estimate sectoral competitiveness in individual euro area countries. Simulations on the impact of productivity shocks in Chinese textiles and machinery suggest that the required adjustment in wages, prices, and factor re-allocation is widely heterogenous across euro area countries on accounts of their different specialization patterns. This raises the question of the distribution of gains and losses from external trade shocks.